Pengaruh Budaya Pop Global Terhadap Nilai dan Identitas Generasi Z pada Masa Kini - Fatimah Fatimah; Santi Aulia Rahma (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
Global pop culture has become a dominant force shaping the values and identities of Generation Z, a cohort raised in the digital age. This generation faces the challenge of integrating global cultural influences with local values. This study aims to analyze the impact of global pop culture on the social values and individual identities of Generation Z through philosophical, idealistic, and empirical lenses. Using a descriptive-narrative method based on secondary data, the article offers strategic solutions, including media literacy education, local culture reinforcement, and global-local collaboration. The findings reveal that global pop culture plays a dual role: enriching perspectives while posing a threat to local values. Multi-stakeholder collaboration is essential to managing these influences wisely.